2006
DOI: 10.1038/nmeth940
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial PO2 measured by delayed fluorescence of endogenous protoporphyrin IX

Abstract: Molecular oxygen is the primary oxidant in biological systems. The ultimate destination of oxygen in vivo is the mitochondria where it is used in oxidative phosphorylation. The ability of this process to produce an amount of high-energy phosphates adequate to sustain life highly depends on the available amount of oxygen. Despite a vast array of techniques to measure oxygen, major (patho)physiological questions remain unanswered because of the unavailability of quantitative techniques to measure mitochondrial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
182
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(192 citation statements)
references
References 29 publications
7
182
1
2
Order By: Relevance
“…Future research should aim to elucidate the mechanisms that lead from decreased O 2 supply to changes in O 2 consumption, and to determine how adaptive or damaging their respective contributions are in the setting of renal I/R. Our group recently developed a method for measuring mitochondrial pO 2 in living cells in vitro by the excitation of endogenous mitochondrial protoporphyrin IX and measurement of the decay of delayed fluorescence (170). If this method proves to be feasible in vivo, it will allow insight into the balance between oxygen supply and oxygen utilization at the intracellular level.…”
Section: Mitochondrial Activity and No-mediated O 2 Consumptionmentioning
confidence: 99%
“…Future research should aim to elucidate the mechanisms that lead from decreased O 2 supply to changes in O 2 consumption, and to determine how adaptive or damaging their respective contributions are in the setting of renal I/R. Our group recently developed a method for measuring mitochondrial pO 2 in living cells in vitro by the excitation of endogenous mitochondrial protoporphyrin IX and measurement of the decay of delayed fluorescence (170). If this method proves to be feasible in vivo, it will allow insight into the balance between oxygen supply and oxygen utilization at the intracellular level.…”
Section: Mitochondrial Activity and No-mediated O 2 Consumptionmentioning
confidence: 99%
“…Recently, it has been reported that the endogenous PpIX selectively accumulates in mitochondria and its delayed fluorescence can be used as an oxygen probe. (Mik et al, 2006) Thus, PpIX as an oxygen probe is also promising and our method is applicable to the PpIX measurements. Consequently, the oxygen concentration change inside the cell at different locations in the organ is possibly measured by this method.…”
Section: Discussionmentioning
confidence: 94%
“…(Nishimura et al, 2007) On the other hand, the new possibility using the delayed fluorescence of endogenous protoporphyrin IX (PpIX) for the oxygen monitoring in cells has been demonstrated. (Mik et al, 2006) These indicate a possibility of the decay analysis for the oxygen dynamics measurement in the cellular level.…”
Section: Introductionmentioning
confidence: 91%
“…5‐ALA is an endogenous amino acid, which is usually synthesized from glycine and succinyl CoA in mitochondria. Induced by supplementation of 5‐ALA in mitochondrion, endogenous porphyrins biosynthesis occurs through several enzyme‐catalyzed steps in cytosol and mitochondrion 6. On the other hand, following systemic administration, exogenous 5‐ALA can also be metabolized into PPIX via the same biosynthesis pathway 7.…”
Section: Introductionmentioning
confidence: 99%